2020
DOI: 10.14295/bds.2020.v23i3.1975
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of remineralization potential of Theobromine and Sodium Fluoride gels on Artificial Caries like lesions

Abstract: Objective: To compare the remineralization potential of theobromine and sodium fluoride gels on artificial caries like lesion. Materials and Methods: Forty longitudinal halves of human mandibular premolars were equally divided into 4 groups of 10 samples each: control group (C), samples were stored in distilled water during the experiment period. The remaining 30 specimens were subjected to demineralization protocol to create caries like lesions. samples were immersed for three days in a demineralizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…Farhad F et al showed similar results. Higher Calcium/ phosphate deposition was found in theobromine solution (3.82 ± 1.83) [16]. Amaenchi B et al reported higher calcium deposition in theobromine and NaF treatments but no statistically significant results were found [12].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Farhad F et al showed similar results. Higher Calcium/ phosphate deposition was found in theobromine solution (3.82 ± 1.83) [16]. Amaenchi B et al reported higher calcium deposition in theobromine and NaF treatments but no statistically significant results were found [12].…”
Section: Discussionmentioning
confidence: 88%
“…Amaenchi B et al evaluated 1.1mmol/l theobromine concentration [12]. Four studies [13,14,15,16], except two studies on dentifrices [17,18] and one study on novel varnish [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with theobromine results in resistance to acid attack. A recent study has shown that theobromine gel had more effective remineralizing potential than fluoride gel [45].…”
Section: Preventive Effect Of Dental Caries By Theobrominementioning
confidence: 99%
“…Segundo Rocha et al (2017), muitas estratégias para a prevenção e tratamento das lesões de cárie foram desenvolvidas, considerando o fluoreto como o principal agente de remineralização. Portanto, existe uma vasta gama de protocolos clínicos (ROCHA et al, 2016;SILVA et al, 2016;SILVA et al, 2017;PUNHAGUIA et al, 2018;CAI et al, 2019;TABOADA-ARANZA;LOAEZA-GALINDO;PALACIOS, 2019;GAVINHA et al, 2020;ELSHERBINE, 2020) utilizando agentes fluoretados como tratamento preventivo e mecanismo inativador de lesões artificiais de cárie.…”
Section: Introductionunclassified